An open-label study of the pharmacokinetics and pharmacodynamics of dabigatran etexilate 150mg once daily in Caucasian patients with moderate renal impairment undergoing primary unilateral elective total knee or hip replacement surgery - Eriksson, Bengt; Feuring, Martin (Thrombosis research, 2016)
Background - In adults with moderate renal impairment (creatinine clearance [CrCl] 30-50mL/min) undergoing total hip or knee replacement (THR/TKR), the recommended dose of dabigatran etexilate is 150mg once daily (qd). We investigated the steady state pharmacokinetics, pharmacodynamics and safety in these patients. - Methods - Single-arm, open-label phase 4 study (NCT01184989) in Caucasian patients receiving dabigatran etexilate 75mg 1-4h after surgery and 150mg qd on days 2-10 (TKR) or days 2-35 (THR). Plasma total dabigatran concentrations (day 6±1) were determined by high-performance liquid chromatography tandem mass spectrometry and indirectly using the commercially available diluted thrombin time (dTT) assay (Hemoclot® Thrombin Inhibitors). - Results - Of 112 patients (mean CrCl 42.5mL/min, age 79.1years, 69.6% female), 100 completed the study. Geometric mean trough and peak dabigatran concentrations were 47.5ng/mL (10th-90th percentile 19.7-120) and 166ng/mL (49.1-364), respectively. There were four major bleeding events and no venous thromboembolic events. Dabigatran concentrations determined from dTT (and falling within the assay range of 50-500ng/mL) underestimated actual values by 7.6% (90% confidence interval 5.3, 9.9), which is within the acceptance limits of ±15%. - Conclusions - These findings in Caucasians with moderate renal impairment undergoing THR or TKR support the use of the 150mg qd dose of dabigatran etexilate. With adequate set-up, calibration and quality control the dTT assay might be appropriate for situations, such as serious bleeding or a need for urgent surgery, where determination of dabigatran levels would be helpful.
Gesehen am 05.03.2020
Available online 16 June 2016